DETERMINAN KEJADIAN STUNTING PADA BALITA - Yosefa Bandur, Paskalinda Maria; Hayati, Zahratul; Blongkod, Fitriani Rahmatismi; Shahab, Fatinah; Mauludiyah, Zaida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Stunting is not only impaired in children's physical growth, but also with brain growth in children. There are more children with low IQs among stunted children than among children who grow up well. The purpose of this study was to determine the relationship between maternal knowledge factors, economic status, and exclusive breastfeeding with the incidence of stunting in the Lima Puluh Kota Pekanbaru Public Health Center Area. The design of this study is a descriptive correlation with crossectional design. This study was conducted in the Area of Lima Puluh Kota Pekanbaru Public Health Center with a population of 1647 people with number of sampling was 94 mothers with inclusion criteria: mothers who have toddlers aged 24-59 months, live in the work area of the Lima Puluh Kota Pekanbaru Public Health Center, and are willing to be respondents. The data collection tool in this study used a questionnaire and the results of the study were processed using the spss. The results in this study found that there was a relationship between maternal knowledge factors and stunting events (p = 0.000), there was a relationship between economic status and stunting events (p = 0.000), and there was a relationship between exclusive breastfeeding and stunting events (p = 0.001). The suggestion from this study is for the Lima Puluh Kota Pekanbaru Public Health Center to develop a schedule to provide health counseling to mothers of toddlers about stunting prevention and prepare a program that help mother to improve the nutrition support by giving vitamins and food.Keywords: Knowledge, Economic, Exclusive Breastfeeding, Stunting